Keep Trying and Leave the Rest to Allah: How Diabetic Indonesian Muslim Adults Manage Self-Care and Religion - Iman Permana (University of Malta, 2014)
Diabetes as a chronic disease, is affecting the person phycically, psychologically and socially, especially due to the complication. many studies have revealed the role of spirituality in maintaining diabetes. this study aimed to explore the influence of religiosity on self-care activity among muslim asults with type 2 diabetes in yogyakarta, indonesia